Implikasi Ketiadaan Sifr Mustadir Ke Atas Pentilawahan Al-quran Braille - Mohd Nur Adzam Rasdi; Muhammad Yusry Affandy Md Isa; Noornajihan Ja‘afar; Khairul Anuar Mohamad; Norakyairee Mohd. Raus (USIM Press, 2024)
Vol. 5 No. 1 (2021)